Masperati - Junaini Johari (2010)
This report details the year-long journey of making Masperati, from its conceptualization to post-production. The report will also shed light on the challenges faced and lessons learnt during this project. Masperati is a 20-minute short film done by student group One Mind Productions. The group comprises three final-year students; Junaini Binte Johari (producer, writer), Valerie Toh Ser-Yi (director, writer) and Jalelah Binte MSAB (editor, writer) and is supervised by Dr. Foo Tee Tuan.